Show that the solution of the initial value problem

$$y''+p(t)y'+q(t)y=g(t),y(t_0)=y_0, y'(t_0)=y_0'$$

can be written as $y=u(t)+v(t)$, where $u$ and $v$ are solutions of the two initial value problems

$$u''+p(t)u'+q(t)u=0, u(t_0)=y_0, u'(t_0)=y_0'$$ $$v''+p(t)v'+q(t)v=g(t), v(t_0)=0, v'(t_0)=0$$

respectively. Be sure to check the initial values.

I was able to show that the solution to the IVP can be written as $y=u(t)+v(t)$ (I believe).

$$(u+v)''+p(t)(u+v)'+q(u+v)=[u''(t)+v''(t)]+[p(t)(u'(t)+v'(t))]+[q(t)(u(t)+v(t))]$$ $$=(u''+pu'+qu)+(v''+pv'+qv)$$ $$=0+g(t)$$ $$=g(t)$$

The problem I am having is checking the initial values. Generally, when it's a simple $$y''+y'-2y=2t, y(0)=0, y'(0)=1$$ type of problem, checking the initial values is very straightforward. For some reason or another, I can't quite seem to check the initial values on this one. I'm sure it is something silly that I'm having a mental block on because it looks different than normal.

Note: this is problem #21 in section 3.7 from Elementary Differential Equations and Boundary Value Problems, Eighth Edition. Boyce, DiPrima.


2 Answers 2


The question asks you to show that $y=u(t)+v(t)$ (with their respective initial conditions) is a solution to the given IVP. Thus, you need only show that $y=u(t)+v(t)$ satisfies (i.e. makes the equality true) the given IVP. You have already done the first part by plugging in $u(t)+v(t)$ into the IVP. The second part is much like the first, verify that the initial value of $u(t)+v(t)$ satisfy the initial values of the IVP.

Note: I am unfamiliar with writing in LaTeX so please excuse my poor notation.

  • $\begingroup$ as to latex - basicaly you just put math symbols between dollar \$ symbols (double dollar if you want the equation to be centered) and if you need special symbols you just take a look here for example: artofproblemsolving.com/Wiki/index.php/LaTeX:Symbols $\endgroup$
    – mm-aops
    May 15, 2014 at 17:35

For the u part: y''+y'-2y=0, y(0)=0,y'(0)=1
Solve the characteristic polynomial, you can find the general solution to be $u=C_1e^{-2t}+C_2e^t$. Put the initial value in, that is $C_1+C_2=0$ and $-2C_1+C2=1$. Subtract the first one from the second one you can find $C_1=-\frac{1}{3}$ then $C_2=\frac{1}{3}$

For the v part: y''+y'-2y=2t, y(0)=0,y'(0)=0
The general solution is $v=C_3e^{-2t}+C_4e^t-t-\frac{1}{2}$. Put the initial value in, that is $C_3+C_4=\frac{1}{2}$ and $-2C_3+C_4=1$. Subtract the first one from the second one you can find $C_3=-\frac{1}{6}$ then $C_4=\frac{2}{3}$

So $u=-\frac{1}{3}e^{-2t}+\frac{1}{3}e^t$ and $v=-\frac{1}{6}e^{-2t}+\frac{2}{3}e^t-t-\frac{1}{2}$ Add them together we have $y=-\frac{1}{2}e^{-2t}+e^t-t-\frac{1}{2}$

For this case $y(0)=-\frac{1}{2}+1-0-\frac{1}{2}=0$ and $y'(0)=-\frac{1}{2}*(-2)+1-0-\frac{1}{2}=1$

Is this what you want?

  • $\begingroup$ Not quite. You used the example to find the solution not the problem. $\endgroup$
    – Vincent
    May 15, 2014 at 16:10
  • 2
    $\begingroup$ For the initial value part, $y(t_0)=u(t_0)+v(t_0)=y_0+0=y_0$ and $y'(t_0)=u'(t_0)+v'(t_0)=y'_0+0=y'_0$ $\endgroup$
    – TooYoung
    May 16, 2014 at 0:39
  • $\begingroup$ I think that's what I was looking! So simple, thanks! $\endgroup$
    – Vincent
    May 16, 2014 at 2:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.